2015
DOI: 10.3233/bmr-140515
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI and X-ray analysis of disc degeneration and paraspinal muscle changes in degenerative spondylolisthesis

Abstract: Decreased anterior disc height and multifidus muscle atrophy are found in the LDS patients and thy could be the cause of LDS. The presence of erector spinae hypertrophy could be a compensatory mechanism to compensate for the instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
(31 reference statements)
2
33
0
Order By: Relevance
“…Disc degeneration did have a correlation with MF muscle area values in our study, but it lost significance in the multivariate analysis. One study on PSMs in degenerative listhesis reported MF muscle atrophy and ES muscle hypertrophy, 35 paralleling the findings in our cohort with IS. Of interest in our study was the finding that while MF muscle atrophy was observed in the entire study cohort compared with controls, it was most pronounced in the patients exhibiting PSC.…”
Section: Lumbar Psm Morphometry and Its Correlationssupporting
confidence: 91%
See 1 more Smart Citation
“…Disc degeneration did have a correlation with MF muscle area values in our study, but it lost significance in the multivariate analysis. One study on PSMs in degenerative listhesis reported MF muscle atrophy and ES muscle hypertrophy, 35 paralleling the findings in our cohort with IS. Of interest in our study was the finding that while MF muscle atrophy was observed in the entire study cohort compared with controls, it was most pronounced in the patients exhibiting PSC.…”
Section: Lumbar Psm Morphometry and Its Correlationssupporting
confidence: 91%
“…
A lterAtions in lumbar paraspinal muscle (PSM) morphometry have been documented in low-back pain (LBP) 6,7,18,20 and degenerative listhesis, 35 with atrophy of the multifidus (MF) muscle frequently reported in these conditions. Paraspinal muscle morphometry has not been analyzed in isthmic spondylolisthesis (IS), a condition with strong physiotherapy connotations, especially in the lower grades.
…”
mentioning
confidence: 99%
“…A recent Chinese study [53] evaluated the MRIs of 149 middle-aged degenerative spondylolisthesis patients and the same total of age- and sex-matched controls. The multifidus muscle atrophy ratio of the patients tended to be significantly lower than those in the control group, whereas the signal intensity ratio of the paraspinal muscles and the erector spinae muscle atrophy ratio were significantly higher than in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Wang and colleagues examined 149 patients with degenerative spondylolisthesis and similarly observed a greater degree of multifidus muscle atrophy compared with controls. 39 In contrast, however, the erector spinae muscles were significantly larger in patients with sagittal imbalance than in patients without deformity, possibly representing a compensatory mechanism to maintain sagittal stability.…”
Section: Discussionmentioning
confidence: 84%
“…Although anatomical studies have illustrated relatively safe corridors for lateral transpsoas approaches, these typical surgical strategies may be less valuable in patients with variable or asymmetrical paraspinal musculature, as has been associated with degenerative spinal diseases. [17][18][19]31,33,39 A variable psoas muscle anatomy is especially concerning because of the intrinsic relationship between the muscle belly and the lumbar plexus.…”
mentioning
confidence: 99%